Evaluation of Analgesic and Neuropharmacological Activity of the Bark of Morus alba L. (Family: Moraceae) - Sultana, Tamanna; Hossain, Md.; Chowdhury, Sadia (Jordan Journal of Pharmaceutical Sciences, 2020)
The aim of the study is to evaluate the analgesic and neuropharmacological properties of the bark of Morus alba L. This plant is well known for its analgesic and antidepressant effects. Analgesic and neuropharmacological activity was conducted at the doses of 200 and 400 mg/kg body weight using Swiss albino mice as animal model. Analgesic activity was investigated using one chemical (acetic acid-induced writhing test) and one thermal (hot plate test) method. In acetic acid-induced writhing test, the standard drug (Diclofenac-Na, 5 mg/kg body weight) showed the inhibition of 89.3%, in which the inhibition of the extract were 57.79% and 54.78% at a doses of 200 and 400 mg/kg body weight, respectively. Overall, the extract showed significant analgesic activity. The neuropharmacological activity was observed by hole cross and open field tests. In hole cross and open field test, the sample significantly decreased the locomotors activity compared to standard drug (Diazepam, 5 mg/kg body weight). Thus, the obtained findings of our present work provide a rationale for the use of this plant for medicinal purposes and encourage us for further investigations to obtain more fruitful results.